2020
DOI: 10.1037/fam0000621
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination, family emotional climate, and African American health: An application of the BBFM.

Abstract: The Biobehavioral Family Model (BBFM) is a biopsychosocial model of health that has been substantiated across multiple studies. However, the findings of those studies are limited given the lack of representation of Black/African American individuals in the samples. Discrimination is a chronic and pervasive stressor for many African American families, yet little is known about connections between discrimination, family relationships, and health. Using Data from the Midlife Development in the United States (MIDU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 69 publications
(112 reference statements)
3
44
0
Order By: Relevance
“…Many studies have now substantiated the role of both intimate partner relationships as well as non-intimate family relationships in understanding the impact of family on health for adults [e.g., ( 33 , 34 )]. Though both operationalizations of family emotional climate—the positivity or negativity, and intensity, of intimate partnerships and of non-intimate family relationships—have been significantly linked to disease activity in tests of the BBFM, studies have tended to support more powerful links for non-intimate family relationships, especially when negative and intense [e.g., ( 29 , 35 , 36 )]. In addition, an application of the BBFM tested with a national, representative, epidemiological U.S. sample operationalized family emotional climate as marital strain and family support, while testing social support received from friends as an additional, contrasting factor ( 37 ).…”
Section: Bbfm Applied To Adult Healthmentioning
confidence: 99%
“…Many studies have now substantiated the role of both intimate partner relationships as well as non-intimate family relationships in understanding the impact of family on health for adults [e.g., ( 33 , 34 )]. Though both operationalizations of family emotional climate—the positivity or negativity, and intensity, of intimate partnerships and of non-intimate family relationships—have been significantly linked to disease activity in tests of the BBFM, studies have tended to support more powerful links for non-intimate family relationships, especially when negative and intense [e.g., ( 29 , 35 , 36 )]. In addition, an application of the BBFM tested with a national, representative, epidemiological U.S. sample operationalized family emotional climate as marital strain and family support, while testing social support received from friends as an additional, contrasting factor ( 37 ).…”
Section: Bbfm Applied To Adult Healthmentioning
confidence: 99%
“…As such, the effects found in this study's models may not be generalized to dissimilar samples. Although prior research has demonstrated the applicability of the BBFM to underserved and underrepresented samples (Priest, McNeil Smith, Woods, & Roberson, 2020; Priest & Woods, 2015; Woods & Denton, 2014), this study does not add to that line of research. Testing the BBFM's pathways longitudinally should consider and intentionally include more diverse samples.…”
Section: Discussionmentioning
confidence: 86%
“…Prior research reported that family support facilitated adherence to medication 25 and improved physical and mental health, 26 well-being, and health outcomes in African Americans. 27 The importance of family support in diabetes self-management perceived by the participants in this study may be associated with AA cultural norms and behaviors that value interdependence, a sense of belonging, and collective identity. 27 AAs rely on a network of family members for emotional and instrumental support to cope with health problems.…”
Section: Discussionmentioning
confidence: 91%
“…27 The importance of family support in diabetes self-management perceived by the participants in this study may be associated with AA cultural norms and behaviors that value interdependence, a sense of belonging, and collective identity. 27 AAs rely on a network of family members for emotional and instrumental support to cope with health problems. 27 Family involvement was also perceived as a source of support in decision-making.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation